The Relationship between Neutrophil Lymphocyte Ratio with Disease Activity in Systemic Lupus Erythematosus - Gede Kambayana; I Gusti Agung Friskha Surya Putra; Pande Ketut Kurniari; Tjokorda Raka Putra (Indonesian Rheumatology Association, 2019)
Background. Systemic Lupus Erythematosus (SLE) is an Autoimmune inflammatory disease that is systemic and chronic inflammation with heterogeneous of history, clinical manifestations, and prognosis. The disease activity of SLE has been proven as a predictor of organ damage and death by evidenced of inflammatory markers involved in this disease. Neutrophil to Lymphocyte Ratio (NLR) is useful for estimating the activity of autoimmune disease and inflammation that easily obtained from blood test and low cost and measurable as new biomarker to assess inflammatory response or activity of SLE. This study aimed to determine the relationship between NRL and Disease Activity based on Mex-SLEDAI in patients SLE. Methods. This study is an analytic study with cross sectional design. It started from November 2016 until March 2017. Mex-SLEDAI and blood sampling used in this study. Result. Total sample in this study is 54 patients with median age was 28.5 years, with mostly female (85,2%). Result analysis with positive correlation between NLR with disease activity on SLE (r=0.399 p=0.003 n=54), thus the Scatter plot shows there is a correlation between NRL with Mex-SLEDAI. Conclusion. Positive correlation between NLR and disease activity of the SLE, the higher of the disease activity/Mex-SLEDAI will be followed by the increase of NLR.